Multilevel-teaching/training practice on GNSS principle and application for undergraduate educations: A case study in China. Issue 1 (1st January 2022) - He, Xiaoxing; Yu, Kegen; Huang, Zhengkai; Montillet, Jean-Philippe; Lu, Tieding; Lan, Xiaoji; Xiao, Genru; Ma, Xiaping; Zhou, Haiping; Chen, Yilin
Abstract: This work discusses a Multilevel-Teaching Practice on GNSS Principle and Application for Undergraduates of Surveying and Mapping in China, underlining the fast development of remote sensing technology. We explore i) the multidisciplinary cross-combination transformation of the traditional GNSS education of remote sensing; ii) we combine theoretical knowledge and practical results in the field of navigation and positioning; iii) we highlight the cutting-edge, intersecting and comprehensive teaching content; innovate the construction of a practical teaching platform for GNSS theory, practice and innovation ability training. A multi-level theoretical and practical curriculum system has been established to strengthen the foundation and professional skills, and cultivate scientific and technological innovation. We propose a teaching method of "Hybrid Online/Offline Teaching", which makes use of the advantages of online/offline teaching form, effectively improving the quality of undergraduate teaching. In terms of practice and innovation ability training, we establish an open, diversified, research-based practice innovation-education platform based on virtual simulated experiments. The implementation of this teaching approach has achieved remarkable results on undergraduate training for GNSS education.